(3TQM eUGHjM GdSfIs - (3Ydj Hf YHO Gddg Hf CMeO GdeYQha HRjf GdYQHs; (3GdHZhj , GdMSjf Hf eSYhO Hf eMeO GdaQGA, eMjj GdSfI CHh eMeO,J (B510 (3g` s ((3eMeO Hf CMeO Hf EHQGgje GdWGcj GdMfaj s)
(3ChdgG (B:s
(3cJGH GdfcGM GdTGH LeY GdTHGH gfG hbO LGA eYfi GdTHjHI CjVkG hgh GdMOGKI hbO jbJUQ hjbGd ajg CjVkG GdHGA aj GdeHGAI GdefRd dCf ddeJRhL EeQCI jfhA HgG efRdG s
(3BNQgG (B:s
(3Ydi eG cGf Ydjg GdfeW GdChd hGdUdGM Ydi eGhQO aj GdCMGOjK YfO NQhL GdegOi hfRhd YjSi Ydjg GdSdGe Efg GdhgGH GdaJGM s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs